2021
DOI: 10.5999/aps.2020.00836
|View full text |Cite
|
Sign up to set email alerts
|

Social media impact in the Match: A survey of current trends in the United States

Abstract: Background Applicants to integrated plastic and reconstructive surgery (PRS) residency in the United States spend exorbitant amounts of time and money throughout the interview process. Outside of first-hand experience through a visiting rotation, applicants utilize various resources in learning about a program. Today’s applicants are “Millennials,” the demographic cohort raised during the information age and proficient with digital technology. The authors evaluated whether programs have a presence on social me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
23
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 17 publications
2
23
1
Order By: Relevance
“…Although previous studies have found that applicants use social media for residency program information, the results of this study demonstrated that a residency program's social media presence only marginally influenced an applicant's decision to apply to that program 2 , 10 , 13 , 14 (Fig. 6 ).…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Although previous studies have found that applicants use social media for residency program information, the results of this study demonstrated that a residency program's social media presence only marginally influenced an applicant's decision to apply to that program 2 , 10 , 13 , 14 (Fig. 6 ).…”
Section: Discussioncontrasting
confidence: 60%
“…Andrew M. Schneider, MD 1 Jackson Tate, BA 2 Michael P. Murphy, MD 1 Kamran Hamid, MD, MPH 1 Terry R. Light, MD, FAOA 1 Adam P. Schiff, MD, FAOA 1 1 Department of Orthopaedic Surgery and Rehabilitation, Loyola University Medical Center, Maywood, Illinois 2 Loyola University Chicago Stritch School of Medicine, Maywood, Illinois E-mail address for A.M. Schneider: Aschneider924@gmail.com…”
mentioning
confidence: 99%
“…Social media utilization by orthopaedic surgery residencies has likely benefited applicants tremendously. Even before COVID-19, >95% of plastic surgery applicants had a social media presence, and 73% followed a residency account 25 . These accounts allow students to gain a better understanding of program culture and fit, which could lead to a more selective application list in line with recommendations from the American Orthopaedic Association Council of Residency Directors for the 2020 to 2021 application cycle 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Social media can also be used to educate followers about topics within a medical specialty [ 15 ]. In a survey of plastic surgery applicants, 89% were interested in educational content and 98% wanted to learn about resident life [ 9 ]. While educational material could help teach on mental health topics from pharmacology to coping skills, for psychiatry, these posts did not increase the total number of followers or engagement score for psychiatry programs.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to COVID-19, a survey found that 10% of respondents reported that information on a program social media profile influenced their residency applications [ 8 ]. The most commonly used platform for interactions with programs, at least according to a 2019 evaluation of plastic surgery applicants [ 9 ], was Instagram.…”
mentioning
confidence: 99%